PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS VIII DI MTS ASWAJA TUNGGANGRI - Husniah, Nayla (Institut Agama Islam Negeri Palangka Raya, 2024)
This research is motivated by the phenomenon of students' understanding of social studies material which is quite low because the learning methods applied are less varied which has an impact on students becoming bored and lacking motivation to learn to study so that student learning outcomes are low. One way that the teacher chooses and uses in learning activities is by applying problem-based learning methods so that students are enthusiastic and not bored and can increase their motivation and learning outcomes. In this study using the type of experimental research with a quantitative approach. The variables used are the independent variable and the dependent variable. The sample in this study was taken from class VIII A as an experimental class with a total of 14 students and class VIII B as a control class with a total of 15 students. Data collection techniques used by researchers are observation, questionnaires, tests, and documentation. Furthermore, data analysis in this study is the research instrument test, prerequisite test, and hypothesis test. Based on the results of the analysis in this study, it shows that the application of problem-based learning methods has a significant effect on student learning motivation in social studies class VIII students at MTs Aswaja Tunggangri, so H0 is rejected meaning that there is a significant effect of problem-based learning methods on class student learning motivation. VIII at MTs Aswaja Tunggangri. The application of problem-based learning methods to student learning outcomes in social studies class VIII students at MTs Aswaja Tunggangri has a significant effect, so H0 is rejected or H1 is accepted, namely there is a significant influence problem-based learning methods on student learning outcomes in social studies class VIII at MTs Aswaja Tunggangri.